2010
DOI: 10.1007/s13280-010-0070-z
|View full text |Cite
|
Sign up to set email alerts
|

Lynx Body Size in Norway is Related to its Main Prey (Roe Deer) Density, Climate, and Latitude

Abstract: We studied the effect of various factors on body size variation of the Eurasian lynx in Norway, using data from 374 lynx collected between 1960 and 1976 and whose locality of capture, year of birth, sex, and age were known. Body size of lynx in Norway was mainly affected by sex and age. Female skull size (and by implication body size) was also positively affected by the availability of its main prey (roe deer) and by latitude, and negatively by the North Atlantic Oscillation (NAO). Male size was not affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…Additionally, S. fatalis does not follow a temporal version of Bergmann's rule, which predicts that larger body sizes are correlated with colder temperatures (Bergmann, ). Many modern carnivores do not in fact follow Bergmann's rule, because their body sizes seem to be indirectly related to climate – and directly linked to competition, prey productivity and food availability (Geist, ; Dayan & Simberloff, , ; McNab, ; Yom‐Tov & Geffen, ; Yom‐Tov et al ., ). Stable isotope data may be useful to help elucidate any interpit differences in prey preference for S. fatalis .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, S. fatalis does not follow a temporal version of Bergmann's rule, which predicts that larger body sizes are correlated with colder temperatures (Bergmann, ). Many modern carnivores do not in fact follow Bergmann's rule, because their body sizes seem to be indirectly related to climate – and directly linked to competition, prey productivity and food availability (Geist, ; Dayan & Simberloff, , ; McNab, ; Yom‐Tov & Geffen, ; Yom‐Tov et al ., ). Stable isotope data may be useful to help elucidate any interpit differences in prey preference for S. fatalis .…”
Section: Discussionmentioning
confidence: 99%
“…(2009), who showed a clear effect of abiotic climatic factors (indexed by NAO) on observed kill rates in snow‐rich areas of the Eurasian lynx distribution. In another relevant study, Yom‐Tov et al. (2010) found that skull size in lynx females was affected positively by roe deer Capreolus capreolus availability and by latitude, and negatively by the NAO index; they concluded that local climate and particularly snow conditions affect lynx skull and body size in females but not in males.…”
Section: Effect Of Climatic Factors On Lynx Genetic Variability In Eumentioning
confidence: 98%
“…We suggest that winter conditions – snow cover depth and duration – explain the variation in Eurasian lynx genetic data better than geographical distance does. It seems that latitude affects the lynx population genetic structure as a proxy for climate: ambient temperature decreases and snow cover increases with latitude (Yom‐Tov et al. 2010).…”
Section: Effect Of Climatic Factors On Lynx Genetic Variability In Eumentioning
confidence: 99%
“…In many birds and mammals, the environmental conditions experienced during their growth period affect food availability and energy expenditure, and ultimately adult body size, as well as a range of other life‐history components (Geist , Read and Gaskin , Ulijaszek et al , Lindstrom ). These conditions include prey availability (Yom‐Tov et al , , ) and other biotic factors that affect food availability, such as prey population density (Pettorelli et al , Mysterud et al , Zedrosser et al ). They also include specific climate variables such as ambient temperature (reviewed by Madsen and Shine , Yom‐Tov et al ) and snow conditions (Stenseth et al ).…”
mentioning
confidence: 99%
“…These conditions include prey availability (Yom‐Tov et al , , ) and other biotic factors that affect food availability, such as prey population density (Pettorelli et al , Mysterud et al , Zedrosser et al ). They also include specific climate variables such as ambient temperature (reviewed by Madsen and Shine , Yom‐Tov et al ) and snow conditions (Stenseth et al ).…”
mentioning
confidence: 99%